“LA’ALLAKUM TASYKURUN”: SEBUAH TINJAUAN DALAM AL-QUR'AN - Hasan, Muhammad; Sagir, Akhmad (CV. Lafadz Jaya, 2024)
The Quran is the holy book of Muslims, containing guidance and teachings of Islam. One term that is frequently used in the Quran is 'la'allakum tasykurun' - so that you may be grateful. Gratitude is a crucial aspect for every Muslim. In essence, being grateful can provide positive benefits for one's spirituality and emotional intelligence. This article introduces a new analysis of the concept of 'la'allakum tasykurun' in the Quran. This concept implies hope and inspiration for Muslims to be grateful and thus needs to be studied. The aim of this article is to understand the expectations placed on Muslims by the term ‘la'allakum tasykurun’ so that it can be studied and practiced. This article employs a qualitative method using text analysis software, ATLAS.ti version 24.1.1.30813. The findings of this study reveal that the term “la'allakum tasykurun” contains significant meaning for Muslims. It conveys the hope that gratitude can be practiced, and therefore, there is a need for education on being grateful. This term is mentioned in the Quran 14 times. There are 12 aspects that cause a person to be grateful for all of Allah's blessings. Muslims are expected to be grateful in any situation because Allah has urged humanity in the Quran to be grateful. This research is expected to provide a valuable contribution to Quranic studies and the Muslim community.